Pultrusion-winding: A novel fabrication method for coreless wound fiber-reinforced thermoset composites with distinct cross-section. (March 2022) - Mindermann, Pascal; Witt, Martin-Uwe; Gresser, Götz T.
Highlights: Integration of intermittent UV pultrusion into coreless filament winding. Novel method for improved winding trajectories validated. Fabrication of composites with set cross-sectional shape without molding tools. Abstract: Bar frameworks integrally manufactured by coreless filament winding are often the superior design solution for voluminous component shapes with distinctive load cases. Numerical simulation results must be validated by full-scale tests due to uncertainties in the mesoscale fiber structure. Pultrusion-winding allows to reduce the geometrical uncertainty of the composite without the limiting use of molds. This is achieved by the combination of intermittent ultraviolet pultrusion, coreless filament winding, and a novel tool trajectory creating method. Straight fiber strand segments are directly cured during winding. This defines their cross-sectional shape and decreases surface irregularities. Around winding points, the curing is temporarily discontinued and the fiber strand remains flexible for hooking. The new fabrication method could be validated on a laboratory scale showing improved mechanical performance and reduced fluctuations in fiber volume ratio in comparison to coreless filament winding.